Prevalence of child marriage and its health effects among Dalit female in a district of province No. 2. - Chaudhary,Khusboo (2019)
ABSTRACT: BACKGROUND: Child Marriage is deep rooted tradition which is followed in any countries. In Nepal it is commonly practiced among the marginalized community. Nepal has committed to eliminate child, early and forced marriage by 2030 in line with target 5.3 of the Sustainable Development Goals. Nepal's marriage law stipulates 20 years as the legal age for marriage for both the sexes, but current records at the Ministry of Health and Population show at least 23 percent of girls getting married off at 15-19 years. Although Nepal banned child marriage in 1963, four out of ten girls are married before they turn 18, according to UNICEF. The figures are even higher among the countries impoverished Dalit's or untouchables who live in remote communities shunned by the mainstream. Thus this study aims to find out the existing prevalence of child marriage and its associated factors among the Terai Dalit in a Gaupalika of Bara district. METHODOLOGY: A cross-sectional study was carried out among 321 Dalit female in three randomly selected wards of Parsauni Gaupalika. Data collection was done by direct Interview with the help of semi-structured questionnaire. Bivariate and multivariate analysis was carried out to find out the potential predictors for child marriage. RESULTS: The prevalence of child marriage among Dalit female was found to be 88% whereas, marital specific prevalence was estimated to be 92.2 %.The prevalence was found to high among the females who did not completed primary education (61.7%).Those who left school due to household works, (p=0.013), education level of respondent (p=0.001) were found to be significantly associated with the child marriage. CONCLUSION: The prevalence of Child Marriage was found to be very much high among the Dalit female of the community. Parents were found to be the most influencing person who pressurized their daughter for the early marriage. Awareness program should be targeted involving parents which may be effective in decreasing child marriage problems. KEY WORDS: Child marriage, Dalit female, Health consequences.